Liquidity Crises and the Market‐Maker of Last Resort - KAHN, CHARLES M.; MARSHALL, DAVID; MCDONALD, ROBERT L. (Journal of money, credit and banking, 2025)
We study market illiquidity in an economy subject to nonfundamental shocks. Asset trading occurs via decentralized bargaining. The model has multiple rational expectations equilibria; we associate certain Pareto‐inferior equilibria with liquidity crises. The government can improve welfare by acting as a “market‐maker of last resort” (MMLR), purchasing assets at above‐market prices. Several policies employed by the United States during the financial crisis are examples of MMLR. We consider “aggressive” and “conservative” MMLR policies. The aggressive policy supports the unique Pareto‐optimal equilibrium. The conservative policy, which embeds a “no‐bailout constraint,” only supports an inefficient equilibrium.